Pedagogies of the body-territory: the construction of feminist knowledge in agroecological production in southeastern Buenos Aires, Argentina (Palimpsesto, 2026)
This research links feminist pedagogies and the concept of body-territory with agroecological production practices in southeastern Buenos Aires, Argentina. The study analyzes the processes of knowledge construction based on the “Cocinas Soberanas” (Sovereign Kitchens) outreach project of the National University of Mar del Plata. A territorialized qualitative methodology with a narrative approach was used, from a critical and gender perspective. The results highlight that women producers played a central role in the construction of agroecological knowledge, promoting a pedagogy of the body-territory. This revalues significant and powerful knowledge for its political, feminist, and social value, leaving a tangible “mark” on these bodies and territories.
Keywords: Feminist pedagogy; Feminist knowledge; Body-territory; Agroecology; Food sovereignty